2020
DOI: 10.18502/jfrh.v14i1.3788
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Pregnancy Interval and the Incidence of Preterm Birth

Abstract: Objective: Preterm birth is associated with high rates of neonatal morbidity and mortality. This study aimed to investigate the relationship between inter-pregnancy interval and the incidence of preterm birth. Materials and methods: In a case-control study, 185 women with preterm delivery and 185 women with term delivery were included. Data including inter-pregnancy interval, demographic characteristics, history of prenatal and neonatal complications, parity, gravidity, type of delivery, and smoking stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…As the interval between births gets shorter, the baby becomes weaker and withered. 12,13 In addition, it has been found that babies born to mothers with shorter birth intervals are at high risk of small for gestational age, 14,15 stillbirth, 16 low birth weight, 17 preterm delivery, 18,19 and birth defects. 20,21 Global countries attempt to slow population growth, but it continues to grow rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…As the interval between births gets shorter, the baby becomes weaker and withered. 12,13 In addition, it has been found that babies born to mothers with shorter birth intervals are at high risk of small for gestational age, 14,15 stillbirth, 16 low birth weight, 17 preterm delivery, 18,19 and birth defects. 20,21 Global countries attempt to slow population growth, but it continues to grow rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, articles were further excluded because of lack of risk estimates ( n = 89), having two or fewer birth spacing strata ( n = 80), birth spacing not measured ( n = 36), irrelevant or nonspecific outcomes ( n = 53), reviews or conference abstracts ( n = 15), short birth spacing ( n = 6), and overlapping population ( n = 4). With additional manual search, 129 studies comprising 46 874 843 participants were ultimately included in the systematic review (Figure S1), including 90 cohort studies, 11‐14,17‐19,34‐116 23 cross‐sectional studies, 10,117‐138 15 case–control studies, 8,139‐152 and 1 cluster‐randomized trial 153 . The baseline characteristics of the eligible studies are presented in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Premature birth is associated with a raised risk of complications among newborns. Preterm delivery problems are the most prevalent cause of death among neonates and the second most prevalent factor of death in children under the age of five years, after pneumonia [2][3][4] . The WHO reports that premature birth affects around 11% of all births worldwide 3 .…”
Section: Inroductionmentioning
confidence: 99%
“…The WHO reports that premature birth affects around 11% of all births worldwide 3 . According to UNICEF, around 860,000 preterm births occur in Pakistan each year, with nearly 102,000 children dying as a result of complications 4 . Despite the fact that there are multiple risk factors for preterm birth, roughly two-thirds of preterm birth cannot be attributable to any of them 5 .…”
Section: Inroductionmentioning
confidence: 99%